Advanced multifunctional magneto-polymeric hybrids - Kongcharoen, Haruethai (Nanyang Technological University, 2022)
Magnetically directed localized polymerization is of immense interest for its extensive impacts and applications in numerous fields. The use of untethered means from external magnetic field to localize initiation of polymerization is a novel concept, with sustainability, efficiency, eco-friendly approach, and wide range potential in both science and engineering. Conventional means for the initiation of polymerization cannot define the desirable location of polymerization during curing process, resulting in poor temporal and spatial control. Herein, the copper immobilized dendrimer-based magnetic iron oxide-silica (MPs-G2@Cu2+) particles are rationally designed as initiators for magnetically localized redox radical polymerization. In this work, the anaerobic adhesive polymerization is composed of three main compositions: triethylene glycol dimethacrylate (TRIEGMA), tert-butyl peroxybenzoate, and MPs-G2@Cu2+. The use of magnet to locate and promote redox free-radical polymerization through the synergistic functions between peroxide and MPs-G2@Cu2+ have been realized. Redox free-radical decomposition mechanism is studied through electron paramagnetic resonance (EPR) characterization, density functional theory (DFT) calculation, as well as nuclear magnetic resonance (NMR) characterization. Magnetic initiator achieved 90 percent monomer conversion after 15 hours polymerization at room temperature, which is comparable to the control system using (Cu(OAc)2) as an initiator and copper source. The mechanical properties of the resulting polymer are considerably reinforced because the MPs-G2@Cu2+ initiators concurrently play another crucial role as nanofillers. The quality assurance of resulting polymer crucially depends on loading of magnetic initiators, and peroxide, temperature, and polymerization time. The magnetically localized polymerization is exploited as a means of patterning. Static and dynamic magnetic polymer patterning can be realized under mild and simple procedure. Magnetic particle size and rheology of prepolymer are tailored to suit the proposed patterning strategies. The working distance (gap between magnet and substrate) and magnetic field strength are also implemented during patterning process toward the patterning design and equipment. According to magnetic field distribution from COMSOL software, the zero vertical gap from substrate provided the highest magnetic flux density. The longer horizontal gap distance is required depended on the magnetic field strength of permanent magnet in order to achieve magnetic adhesive polymer pattern without the interference of magnetic field distribution between two magnets. This strategy provides a novel approach for magnetically localized polymerization, which can be used for advanced adhesives under hazard-free condition and patterning under mild conditions.